Pengaruh Promosi dan User Friendly Terhadap Keputusan Pembelian Pada Aplikasi ShopeeFood Batam - Ichsan Dwibowo; Nora Pitri Nainggolan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to examine the influence of promotional strategies and user-friendliness on consumer purchasing decisions on the ShopeeFood platform in Batam City. The research used a descriptive quantitative approach, involving 100 actively transacting respondents, selected through purposive sampling based on Lemeshow's calculation guidelines to ensure sample representativeness. Data were collected through a structured questionnaire and analyzed using a series of validity and reliability tests, classical assumption checks, multiple linear regression, and hypothesis testing using t- and F-tests. The research findings indicated that promotions contributed 42.4% to purchasing decisions, while user-friendliness contributed 26.0%. The coefficient of determination (R²) of 78.9% confirmed that these two variables collectively explained most of the variation in purchasing behavior. The results of the t- and F-tests confirmed that promotions and user-friendliness had a significant influence, both partially and simultaneously, emphasizing the importance of integrating effective digital marketing strategies and an intuitive application interface to drive consumer decisions on ShopeeFood in Batam City.